Visible Reflectance Hyperspectral Imaging: Characterization of a Noninvasive, in Vivo System for Determining Tissue Perfusion - Zuzak, Karel J; Schaeberle, Michael D; Lewis, E. Neil; Levin, Ira W (Analytical chemistry (Washington), 2002)
We characterize a visible reflectance hyperspectral imaging system for noninvasive, in vivo, quantitative analysis of human tissue in a clinical environment. The subject area is illuminated with a quartz−tungsten−halogen light source, and the reflected light is spectrally discriminated by a liquid crystal tunable filter (LCTF) and imaged onto a silicon charge-coupled device detector. The LCTF is continuously tunable within its useful visible spectral range (525−725 nm) with an average spectral full width at half-height bandwidth of 0.38 nm and an average transmittance of 10.0%. A standard resolution target placed 5.5 ft from the system results in a field of view with a 17-cm diameter and an optimal spatial resolution of 0.45 mm. The measured reflectance spectra are quantified in terms of apparent absorbance and formatted as a hyperspectral image cube. As a clinical example, we examine a model of vascular dysfunction involving both ischemia and reactive hyperemia during tissue reperfusion. In this model, spectral images, based upon oxyhemoglobin and deoxyhemoblobin signals in the 525−645-nm region, are deconvoluted using a multivariate least-squares regression analysis to visualize the spatial distribution of the percentages of oxyhemoglobin and deoxyhemoglobin in specific skin tissue areas.